Usefulness of tungsten shield in mammography - Gyu Kim, Chang (International Journal of Engineering and Technology, 2018)
Background/Objectives: In order to minimize unnecessary artifacts and medical radiation dose for acquiring final diagnostic medical image with high diagnostic value in X-ray mammography, a tungsten shield was produced to evaluate the usefulness of clinical application.Methods/Statistical analysis: The radiation dose at the time of mammography was measured in the same posture as breast cancer examination in a clinical hospital for health screening. In the R - CC, L - CC. R - MLO, L- MLO posture mammography, the distribution of radiation dose for each part by placing a glass dose device at the breast position with the breast equivalent phantom. In order to reduce measurement error, mammography was repeated five times.Findings: When the eco-friendly shield was used, the average dose was 40 Â± 0.34Î¼Gy, which showed a radiation dose reduction efficiency of 64.6% and a reduction factor of 2.8. Using eco-friendly shield tungsten shield, reproducibility of fibrin was 4.5, reproducibility of specks was 4.0, and reproducibility of the mass was 4.0 Â± 0.2, resulting in 12.5, exceeding the approved acceptance criteria of 10.Improvements/Applications: This result is expected to be used as an important basic data for predicting patient's radiation dose, determining test method and decreasing medical radiation dose in future breast cancer examination.Â Â